Find the sum of the given polynomials.
2mn + 4n 2 and 5m 2 - 7mn

Question

Asked 5/4/2015 10:44:02 AM

Updated 6/6/2015 12:33:30 PM

3 Answers/Comments

This answer has been confirmed as correct and helpful.

s

wiwit|Points 688|

Andrew.|Points 51544|

scijoe21|Points 2275|

jeifunk|Points 48277|

= 5h - 3k

Question

Asked 5/4/2015 10:44:02 AM

Updated 6/6/2015 12:33:30 PM

3 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

3

-8 + b - (5 + b^2)

= -8 + b - 5 - b^2

= -13 + b - b^2

= -8 + b - 5 - b^2

= -13 + b - b^2

Added 5/4/2015 7:24:26 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:29:48 PM]

3

2p^2 + 3p - 4 - (-2p^2 - 3p + 4)

= 2p^2 + 2p^2 + 3p + 3p - 4 - 4

= 4p^2 + 6p - 8

= 2p^2 + 2p^2 + 3p + 3p - 4 - 4

= 4p^2 + 6p - 8

Added 5/4/2015 7:26:36 PM

This answer has been confirmed as correct and helpful.

3

2m - [n - (m - 2n)]

= 2m - [n - m + 2n]

= 2m - 3n + m

= 3m - 3n

= 2m - [n - m + 2n]

= 2m - 3n + m

= 3m - 3n

Added 5/4/2015 7:28:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:34:48 PM]

Simplify (x 2 y) 3.

Question

Not Answered

Updated 4/27/2015 6:36:31 PM

1 Answer/Comment

(x^2y)^3

= x^6y^3

= x^6y^3

Added 4/27/2015 6:36:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [4/27/2015 6:49:41 PM]

Simplify.
(-4·3·2)2 **Weegy:** (-4 * 3 * 2)^2 = (-24)^2 = 576 **User:** Simplfy.
(a 2 b 3)4 **Weegy:** (a^2 b^3)^4 = a^8 b^12 **User:** Simplify.
(-7p)3 **Weegy:** (-7p)^3 = (-7p)(-7p)(-7p) = (49p^2)(-7p) = -343p^3 **User:** The expression (2x2)3 is equivalent to _____. (More)

Question

Not Answered

Updated 6/6/2015 11:49:44 AM

1 Answer/Comment

Evaluate (x + y )^0 for x = –3 and y = 5. User: Simplify.
n^6 • n^5 ÷ n^4 • n^3 ÷ n^2 • n

Question

Updated 4/27/2015 12:02:13 PM

2 Answers/Comments

(x + y )^0 for x = –3 and y = 5;

(-3 + 5)^0

= 2^0

= 1

(-3 + 5)^0

= 2^0

= 1

Added 4/27/2015 12:02:02 PM

This answer has been confirmed as correct and helpful.

n^6 • n^5 ÷ n^4 • n^3 ÷ n^2 • n

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

Added 4/27/2015 12:02:13 PM

This answer has been confirmed as correct and helpful.

Evaluate the following expression.
(-6)^-2

Question

Not Answered

Updated 5/4/2015 12:54:35 PM

1 Answer/Comment

(2n^3 + 4n^2 - 7) + (-n^3 + 8n - 9)
**Weegy:** (2n^3 + 4n^2 - 7) + (-n^3 + 8n - 9)
= 2n^3 + 4n^2 - 7 - n^3 + 8n - 9
= n^3 + 4n^2 + 8n - 16 (final answer) (More)

Question

Expert Answered

Updated 5/8/2015 2:31:50 PM

0 Answers/Comments

32,204,620

questions answered

There are no comments.